"Food company sponsors are kind, generous and cool": (Mis)conceptions of junior sports players - King Lesley; Bauman Adrian E; Baur Louise A; Kelly Bridget; Chapman Kathy; Smith Ben J (BMC, 2011)
Abstract Background Children's exposure to unhealthy food marketing influences their food knowledge, preferences and consumption. Sport sponsorship by food companies is widespread and industry investment in this marketing is increasing. This study aimed to assess children's awareness of sport sponsors and their brand-related attitudes and purchasing intentions in response to this marketing. Methods Sports clubs known to have food sponsors and representing the most popular sports for Australian children across a range of demographic areas were recruited. Interview-based questionnaires were conducted at clubs with children aged 10-14 years (n = 103) to examine their recall of local sports club and elite sport sponsors, and their attitudes towards sponsors and sponsorship activities. Results Most children (68%) could recall sponsors of their sports club, naming a median of two sponsors, including a median of one food company sponsor each. Almost half (47%) of children could recall any sponsors of their favourite elite sporting team. Children aged 10-11 years were more likely than older children to report that they thought about sponsors when buying something to eat or drink (P < 0.01); that they liked to return the favour to sponsors by buying their products (P < 0.01); and that sponsors were 'cool' (P = 0.02). Most children had received a voucher or certificate from a food or beverage company to reward sport performance (86% and 76%, respectively). Around one-third of children reported liking the company more after receiving these rewards. Conclusions Children's high recall of food and beverage company sport sponsors and their positive attitudes towards these sponsors and their promotions is concerning as this is likely to be linked to children's food preferences and consumption. Limiting children's exposure to this marketing is an important initiative to improve children's nutrition.